Mathematical Modeling and CFD Analysis for Protype Model Development of a Low-cost Hybrid Power Operated Mini Kitchen Chimney for Rural Households - Dr. Ashis Acharjee; Abhishek Bhadauria; Krushnakant Borude (International Journal of Energy and Thermal Applications, 2023)
Home chimneys remove pollution by products of fossil fuels from the atmosphere. Today's environmental problems are worsening rapidly due to technology and population growth. Thus, researchers developed a hybrid micro kitchen chimney to help rural residents at a low cost. This small hybrid chimney simplifies rural cooking. A kitchen chimney is the best way to remove smoke, grease, stink, stains, oil droplets, and more from the kitchen. It helps ventilate the kitchen. Choosing the best option is difficult. This study introduces a hybrid mini-kitchen chimney for rural areas to improve performance, reduce household air pollution, and save energy. Our present work uses CFD to estimate and assess the flow mechanics in and around the kitchen chimney region. CFD study results will inform kitchen plan refinement. Sunlight powers the hybrid chimney
Keywords: CFD; Solar power; hybrid mini kitchen chimney; optimum performance; rural areas